A New Concept for Classifying Skull Base Defects for Reconstructive Surgery - Yano, Tomoyuki; Okazaki, Mutsumi; Tanaka, Kentarou; Iida, Hideo; Aoyagi, Masaru; Tsunoda, Atsunobu; Kishimoto, Seiji (Journal of Neurological Surgery Part B: Skull Base, 2012)
To classify the defects of the skull base, we present a new concept that is intuitive, simple to use, and consistent with subsequent reconstructive procedures. The centers of defects are determined in the anterior (I) or middle (II) skull base. The defects are classified as localized in the defect's center (Ia, IIa) or extended horizontally (Ib, IIb) or vertically (Ic, IIc) from the defect's center. Accompanying defects of the orbital contents and skin are indicated by “O” and “S,” respectively. An algorithm for selecting subsequent reconstructive procedures was based on the classification. Using the new system, we retrospectively reclassified 90 skull base defects and examined how the defect classifications were related to the reconstructive flaps used and postoperative complications. All defects were reclassified with the new system without difficulty or omission. The mean correlation rate was high (88%) between the flaps indicated by the new classification and the flaps that had actually been used. The rate of postoperative complications tended to be higher with Ia, Ic, and IIb defects and combined defects. Our new classification concept can be used to classify defects and to help select flaps used for subsequent reconstructive procedures.
Keywords: skull base; skull base defect; classification; reconstructive surgery